Exploration of Anime “A Silent Voice” as a Media for Mental Health Education: Thematic Analysis of Audience Reactions on YouTube - Kurnia, Galuh Mega; Hermawan, Nuri; Muthmainnah, Muthmainnah; Qomaruddin, Mochammad Bagus (Universitas Airlangga, 2025)
Background: A Silent Voice tells the story of Shoya Ishida, a teenager involved in bullying Shoko Nishimiya, a hearing-impaired girl. The anime touches on deep themes such as bullying, guilt, self-acceptance, and healing, making it a valuable medium for mental health discussion and education. Objectives: To explore the anime A Silent Voice as a medium for mental health education. Methods: This study used social media reactions with a thematic analysis approach. The research began with a YouTube search for videos discussing the anime, resulting in four videos with the highest views and comments. Audience comments from June to August 2024 were extracted and selected, then analyzed to identify common themes related to anime and mental health. Results: Discussion comments related to the anime A Silent Voice had 237 identified conversations discussing anime and mental health. The major topics discussed in the discussion are bullying; self-acceptance; suicide; the impact of watching anime; opinions and lessons learned from anime; and opinions on characters in anime. The conversations highlighted the profound impact on viewers, especially those who have experienced depression, bullying, or isolation. Conclusions: The anime A Silent Voice is seen as a highly impactful and emotionally resonant movie that addresses themes of self-acceptance, empathy, and personal growth, which leaves a deep impression on its audience. This research is limited to discussions on YouTube comments. Further research must be conducted to determine the effectiveness of the anime A Silent Voice on viewer’s mental health.